2011
DOI: 10.1038/gt.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial gene delivery using molecular cardiac surgery with recombinant adeno-associated virus vectors in vivo

Abstract: We use a novel technique that allows for closed recirculation of vector genomes in the cardiac circulation using cardiopulmonary bypass, referred to here as molecular cardiac surgery with recirculating delivery (MCARD). We demonstrate that this platform technology is highly efficient in isolating the heart from the systemic circulation in vivo. Using MCARD, we compare the relative efficacy of single-stranded (ss) adeno-associated virus (AAV)6, ssAAV9 and self-complimentary (sc)AAV6-encoding enhanced green fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 21 publications
(21 reference statements)
1
53
0
Order By: Relevance
“…Recently, White et al demonstrated an extremely high transduction efficiency in the majority of cardiomyocytes in sheep while minimizing collateral organ exposure using a retrograde recirculation method during cardiopulmonary bypass surgery (28). Retrograde coronary infusion has been shown to be safe, when performed by a trained and experienced surgeon.…”
Section: Figurementioning
confidence: 99%
“…Recently, White et al demonstrated an extremely high transduction efficiency in the majority of cardiomyocytes in sheep while minimizing collateral organ exposure using a retrograde recirculation method during cardiopulmonary bypass surgery (28). Retrograde coronary infusion has been shown to be safe, when performed by a trained and experienced surgeon.…”
Section: Figurementioning
confidence: 99%
“…White et al reported a novel surgical procedure (MCARD) that allowed for closed recirculation of AAV vectors in the cardiac circulation using cardiopulmonary bypass in sheep (White et al, 2011). This approach resulted in highly efficient, cardiac specific gene transfer using the scAAV6 vector.…”
Section: Vehicles Of Gene Deliverymentioning
confidence: 99%
“…In murine and rodent models single stranded (ss) AAV6, self-complementary (sc) AAV6 and ssAAV9 are capable of long term expression after transference of genetic material to the cardiomyocytes, however it has not been reproduced in large animals. Recently it has been proposed that the highest levels of expression in large animals, are obtained using scAAV6 vectors, delivered through surgical methods (White et al, 2011).…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…The system in which the greater effectiveness of transference has been observed, consist of perfusion of the myocardium by surgical methods, a technique known as Molecular Cardiac Surgery with Recirculating Delivery (MCARD); this consists in the establishment of conventional cardiopulmonary bypass, with isolation of the heart circulation and retrograde perfusion through the coronary sinus. MCARD allows performing surgical procedures in the heart while the transference of genetic material is occurring (Hayase et al, 2005;Katz et al, 2010;Raake et al, 2004;White et al, 2011). An option to avoid the ectopic expression of the transferred gene is to put the expression of the transferred gene under the control of a specific cardiac promoter, as is the case of the human cardiac calsequestrin gene (hCasq2) (Reyes-Juarez et al, 2007).…”
Section: Intra-organ Transferencementioning
confidence: 99%